Pendampingan Praktikum Asam dan Basa: Upaya Meningkatkan Keterampilan Laboratorium Siswa Kelas 12 - Najwa, Fatri; Hujjatusnaini, Noor; Erawaty, Yenny (Yayasan Kajian Riset dan Pengembangan RADISI, 2024)
Effective chemistry learning requires practicum activities to improve students' science process skills, especially in acid and base materials. Practicum has an important role in supporting learning that involves direct experience and in-depth understanding of concepts. However, obstacles such as limited laboratory facilities and lack of motivation often interfere with practicum implementation. This study aims to assist XII grade students of SMA Muhammadiyah 1 Palangka Raya in carrying out chemistry practicum with a qualitative approach, through activities that include briefing, material explanation, practicum implementation, and evaluation. The results showed that practicum activities encourage students to learn actively and develop laboratory skills, including the skill of testing pH using chemical and natural materials available in the surrounding environment. Group discussions and presentations as part of the evaluation also helped improve students' understanding of acid-base concepts and scientific communication skills. This practicum assistance is expected to improve the quality of chemistry learning in schools and provide meaningful learning experiences for students.